Studi Riview : Media Pembelajaran Biologi Dalam Meningkatkan Motivasi Belajar Siswa Terhadap Kesadaran Lingkungan Sekitar - Revi Ruth Susanty; Putri Nora; Marina Azzahra Nasution; Aryediatami Naura Kamila; Ashar Hasairin (Universitas Sebelas Maret, 2025)
This literature study aims to find out and analyze the role of various learning media in increasing student learning motivation towards environmental awareness. This study uses a literature review method, namely by collecting research articles found in Pubmed and Google Scholar from 2019-2024 using the keywords